2006
DOI: 10.1371/journal.ppat.0020005
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Group A Streptococci Reveals a Mutation That Modulates Global Phenotype and Disease Specificity

Abstract: Many human pathogens produce phenotypic variants as a means to circumvent the host immune system and enhance survival and, as a potential consequence, exhibit increased virulence. For example, it has been known for almost 90 y that clinical isolates of the human bacterial pathogen group A streptococci (GAS) have extensive phenotypic heterogeneity linked to variation in virulence. However, the complete underlying molecular mechanism(s) have not been defined. Expression microarray analysis of nine clinical isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

40
652
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 417 publications
(696 citation statements)
references
References 45 publications
40
652
1
3
Order By: Relevance
“…Traditionally this "rheumatogenecity" has been considered to be a feature of strains belonging to certain M serotypes (the serotypes M3 and M18 have been related to ARF). Recent genome-wide analyses of group A streptococci have demonstrated that the heterogeneity in disease severity caused by group A streptococci is mediated by genetic variation in a signal transduction system that affects the expression of virulence factors (36,37). The combination of a susceptible host and a virulent group A Streptococcus may induce an exaggerated immune response, leading to valvular heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally this "rheumatogenecity" has been considered to be a feature of strains belonging to certain M serotypes (the serotypes M3 and M18 have been related to ARF). Recent genome-wide analyses of group A streptococci have demonstrated that the heterogeneity in disease severity caused by group A streptococci is mediated by genetic variation in a signal transduction system that affects the expression of virulence factors (36,37). The combination of a susceptible host and a virulent group A Streptococcus may induce an exaggerated immune response, leading to valvular heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…The globally disseminated M1T1 clone of group A Streptococcus (GAS) is linked with rare but life-threatening syndromes of necrotizing fasciitis and toxic shock syndrome 1 . Mutations in the GAS control of virulence regulatory sensor kinase (covRS) operon are associated with severe invasive disease, abolishing expression of a broad spectrum cysteine protease (SpeB) 2,3 and allowing the recruitment and activation of host plasminogen on the bacterial surface 4 . Here we describe how bacteriophage-encoded GAS DNase (Sda1), which facilitates the pathogen's escape from neutrophil extracellular traps (NETs) 5,6 , serves as a selective force for covRS mutation.…”
mentioning
confidence: 99%
“…In the M1T1 GAS clone, the transition from local to systemic infection can be linked to mutations in the two-component covRS regulator. The effect of these mutations is a distinct shift in the transcriptional profile of invasive GAS isolates compared to mucosal (throat) isolates 3 . The covRS mutation and changes in gene expression are recapitulated upon subcutaneous challenge of mice and analysis of GAS disseminating to the spleen in comparison with those in the original inocolum 3 .…”
mentioning
confidence: 99%
“…To determine the basis for hyper-encapsulation, in one experiment, we undertook genome sequencing of representative isolates from lymph node and spleen from a single mouse. Although isolates from the spleen demonstrated a mutation in covR , which might be predicted from many other studies [9,32], the hyper-encapsulated GAS variants in the draining lymph node demonstrated a deletion in the hasABC promoter which leads to loss of one of the reported CovR binding sites[25], thereby de-repressing capsule production specifically [25]. The hyper-encapsulated promoter mutant strain (P2) had enhanced fitness with regard to transit to, and/or retention in, the draining lymph node consistent with the reported interaction between hyaluronan and the lymphatic receptor LYVE-1 [22].…”
Section: Discussionmentioning
confidence: 75%
“…One of the most-studied two component GAS regulatory systems is CovRS, which is responsible for regulating 10–15% of the GAS genome, and repressing the expression of virulence genes such as those of the hasABC operon that result in expression of hyaluronan capsule [8]. CovRS plays an important role in the systemic dissemination of GAS and spontaneous mutations have been demonstrated in hyper-encapsulated emm 1 GAS isolates from spleen during experimental in vivo infection [9,10]. …”
Section: Introductionmentioning
confidence: 99%